'Wacana' dan 'cerita' dalam novel Pujangga Melayu oleh Mohd. Affandi Hassan - Abdul Rani, Mohd Zariat (Universiti Putra Malaysia Press, 2008)
The function of literary works, specifically that of fictional narratives, has been a source of debate in Western and Eastern civilisations throughout the ages. In ancient Greece for example, this issue sparked a conflict between the philosophical schools of Plato and Aristotle, who both had contrasting views on the role and contribution of literary works to the formation of a culturally civilised society. The Malay literary tradition is no exception; Braginsky (1993) states that since the 16th and 17th centuries, Malays have been aware of the functional value of literature, which among other functions serves to teach, and to enlighten mankind with knowledge. It is important to note that the same issue is still a matter of debate in contemporary Malay literature. Chief amongst those who regularly foreground the issue is Mohd. Affandi Hassan (herafter Hassan), a renowned Malaysian literary critic and creative writer. As a literary critic, Hassan generated the notion of ‘Persuratan Baru’, a notion that amongst other principles urges authors of Malay literary works to prioritise the transmittance of knowledge. Naturally, this invites scrutiny, especially given the context of Hassan being a creative writer himself; with such a standing (as a literary critic and creative writer) the question that immediately springs to mind is whether Hassan heeds his own call. In this light, this article will analyse one of Hassan’s works based on his own analytical framework – Persuratan Baru – in an effort to determine whether the construction of said work truly takes into account his own identification of the function of literary works, that is as a medium of knowledge. Therefore, Hassan’s novel Pujangga Melayu (1997) (henceforth Pujangga…) will be utilised as a study material. By using PB which distinguishes clearly between ‘knowledge’ (ilmu) and ‘narrative’ (cerita) as an analytical framework, my findings answer the question brought up earlier that Hassan has indeed practiced what he has preached, by presenting Pujangga… as a concrete manifestation of his literary notion - ‘Persuratan Baru’.